Impact of Blunted Perception of Dyspnea on Medical Care Use and Expenditure, and Mortality in Elderly People - Ebihara, Satoru; Niu, Kaijun; Ebihara, Takae; Kuriyama, Shinichi; Hozawa, Atsushi; Ohmori-Matsuda, Kaori; Nakaya, Naoki; Nagatomi, Ryoichi; Arai, Hiroyuki; Kohzuki, Masahiro; Tsuji, Ichiro (Frontiers in Physiology, 2012)
Dyspnea is an alarming symptom responsible for millions of patient visits each year. Poor perception of dyspnea might be reasonably attributed to an inappropriately low level of fear and inadequate earlier medical treatment for both patients and physicians, resulting in subsequent intensive care. This study was conducted to evaluate medical care use and cost, and mortality according to the perception of dyspnea in community-dwelling elderly people. We analyzed baseline data from a community-based Comprehensive Geriatric Assessment (CGA) in 2002. The perception of dyspnea in 479 Japanese community-dwelling elderly people with normal lung function was measured in August 2002. The sensation of dyspnea during breathing with a linear inspiratory resistance of 10, 20 and 30 cmH2O/L/s was rated using the Borg scale. According to the perception of dyspnea, we divided the elderly into tertiles and compared all hospitalizations, out-patient visits, costs and death through computerized linkage with National Health Insurance (NHI) beneficiaries claims history files between August 2002 and March 2008. In-patient hospitalization days and medical care costs significantly increased with the blunted perception of dyspnea, resulting in an increase in total medical-costs with blunted perception of dyspnea. With low perception group as reference, the hazard ratios of all cause mortality were 0.65 (95%CI 0.23-1.89) for intermediate perception group and 0.31(0.10-0.97) for high perception group, indicating the mortality rate also significantly increased with the blunted perception of dyspnea after multivariates adjustment (p=0.04). The blunted perception of dyspnea is related to hospitalization, large medical costs and all-cause mortality in community-dwelling elderly people. These findings provide a rational for preventing serious illness with careful monitoring of objective conditions in the elderly.